The Impact of Reflective Maternal Method toward Receptive Communication Ability on Student with Hearing Impairment - Erlin Fitria; Oktavia Hardiyantari (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
Communication is a bridge to connect human being. Through communication relationships will be established among people. People will always carry out the process of communication with others during their lifetime. This communication process is not a difficult to do for those who do not experience hearing limitation, but it will become a more complex process for people with hearing impairment. Limitations in listening to sound stimulus make the communication process a little hampered because people with hearing impairment become more difficult to be able to understand the contents of the conversation spoken by the other people. The ability to understand the meaning of what is uttered by the other people in the communication process is called receptive communication. Failure in receptive communication will have an impact on other developments such as in terms of psychological, social, intelligence and economic development. The purpose of this study was to determine the effect of the reflective maternal method on receptive communication skills of students with hearing impairment. The method used was quasy experimental with a randomized control group pretest-posttest design. The results of the study based on the Mann-Whitney test were obtained by Asymp. Sig. (2-tailed) 0.002 with an error level of 0.05 then 0.002 <0.05 means that Ho is rejected, and Ha is accepted, so there is a significant difference between the control group and the experimental group. In conclusion, the reflective maternal method influences the improvement of receptive communication on students with hearing impairment.